Relations between schools and immigrant and refugee families: the role(s) of school principals as seen through a territorial approach - Geneviève Audet; Marc Donald Jean Baptiste (Educazione Interculturale)
A previous meta-analysis of Quebecois studies highlighted the ways in which considering the diverse profiles and needs of families can positively impact the socio-educational experiences of immigrant-origin students. However, it has also been documented that many school staff view immigrant and refugee families through a lens characterized by tension or even from a deficit-based and essentializing perspective. While school principals must play a certain prescribed role in relations between schools and families, little attention has been given to how they actually assume this role. In this article, drawing from a corpus of stories of practice collected from primary school principals (n=9), we identify nine roles these individuals assume in their relations with immigrant and refugee families. We then interpret these roles through the lens of a territorial approach, allowing us to identify three types of territorialities (benevolent, ambivalent, and hostile) which offer a renewed perspective on the prescribed role of principals with these families.